TING TINGKAT PARTISIPASI MASYARAKAT DALAM MENJAGA KESEHATAN LINGKUNGAN DI PERMUKIMAN NELAYAN KELURAHAN CILINCING, JAKARTA UTARA - Indri Apriliani; Hotimah, Oot; Badaruddin Mataburu, Ilham (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2022)
Fisherman settlements in Cilincing Village, North Jakarta are desenly populated settlements. The role of the community in maintaining environmental health is very necessary to prevent the spread of disease. In 2020 the number of healthy and larva-free houses in RW 04 Cilincing Village is still low. This study aims to determine the level of community participation in maintaining environmental health in fishermen’s settlements, Cilincing Village, North Jakarta. This research method is descriptive research with survey approach. The results showed that the level of community participation at the planning stage had a score of 43.62% (medium), the level of community participation at the implementation stage has a score of 50.16% (medium), and the level of community participation at the evaluation/monitoring stage has a score of 46.46% (medium). While the level of community participation as a whole from the planning, implementation, and evaluation/monitoring stages has a score of 47.25% (medium). The main thing that causes the level of community participation to be in the moderate category is due to the uneven distribution of information, as well as the lack of public awareness in preventing dengue and waste management.